2021
DOI: 10.1002/osp4.479
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent social rhythms are associated with abdominal adiposity after involuntary job loss: An observational study

Abstract: Objective: Unemployment is an established risk factor for obesity. However, few studies have examined obesity-related health behavior after involuntary job loss specifically. Job loss confers a disruption in daily time structure that could lead to negative metabolic and psychological outcomes through chronobiological mechanisms. This study examines whether individuals with unstable social rhythms after involuntary job loss present with higher abdominal adiposity than individuals with more consistent social rhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(105 reference statements)
1
2
0
Order By: Relevance
“…Social rhythms are operationalized as both the volume and daily variability in the timing of habitual daily activities, including work, social activities, meals, exercise, TV, and retiring to bed. Our group recently demonstrated that less consistent social rhythms were cross-sectionally associated with higher WC in nondepressed unemployed individuals [9]. These findings are consistent with research showing that the loss of daily social rhythms in children may be a significant factor for weight gain over summer breaks [10], when students often lose daytime routine and structure.…”
Section: Introductionsupporting
confidence: 85%
“…Social rhythms are operationalized as both the volume and daily variability in the timing of habitual daily activities, including work, social activities, meals, exercise, TV, and retiring to bed. Our group recently demonstrated that less consistent social rhythms were cross-sectionally associated with higher WC in nondepressed unemployed individuals [9]. These findings are consistent with research showing that the loss of daily social rhythms in children may be a significant factor for weight gain over summer breaks [10], when students often lose daytime routine and structure.…”
Section: Introductionsupporting
confidence: 85%
“…However, behavioral-social rhythms have not been widely applied to other health outcomes, including CVD risk factors, with only a few studies exploring this area. For example, a study found that lower behavioral-social rhythm regularity was associated with larger waist circumference for individuals with lower levels of depressive symptoms after an involuntary job loss (28). Another study found that individuals who received an intervention that included a lifestyle component to stabilize behavioral-social rhythms had greater decreases in BMI compared with those who were assigned to a control group (43).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the occurrence of these behaviors, the regularity in the timing of these behaviors (i.e., behavioralsocial rhythm regularity) is hypothesized to contribute to the stable entrainment of endogenous circadian rhythms and promote better health outcomes (23)(24)(25)(26)(27). For example, worse behavioral-social rhythm regularity may increase risk for individual CVD risk factors like greater abdominal adiposity (28). These CVD risk factors (obesity, hypertension, impaired glucose tolerance, hypertriglyceridemia, and decreased highdensity lipoprotein [HDL] cholesterol) tend to co-occur in a condition called metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%